RESPIRATORY DISEASE ASSOCIATED WITH BIOMASS SMOKE EXPOSURE IN RURAL WOMEN - PRIYA, JYOTI; NIRALA, RAKESH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective:The aim of this study was to evaluate the effect of biomass fuel combustion on pulmonary function tests (PFTs) and comparing the PFTs between biomass users and Liquefied petroleum gas (LPG) users. Method: 150 healthy non-smoking women were randomly selected within the age group of 21-50 years for this cross-sectional study. The study group comprised of 75 subjects who used biomass fuel for cooking (Biomass users) and 75 age matched subjects who were not exposed to biomass served as the controls (LPG users). . The anthropometric data i.e., age, height, weight, blood pressure, respiratory rate was noted and the subjects pulmonary functions were evaluated using RMS Medspiror. Result: The lung function parameters were significantly lower in the study group, exposed to biomass fuel than the controls FEV1 (p<0.001); FEV1/FVC (p<0.001) and PEFR (p<0.001), except FVC (p<0.338). The evaluation of PFTs suggested the increased risk to the obstructive type of pulmonary disease in biomass users. Conclusion: The reduction in the pulmonary function in the biomass exposed women could be due to high exposure to biomass pollutants with inadequate ventilation in cooking area leading to chronic pulmonary disease.